2009
DOI: 10.1152/ajpendo.00230.2009
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of estrogen, age, and visceral fat on pulsatile growth hormone secretion in healthy women

Abstract: Relative effects of estrogen, age, and visceral fat on pulsatile growth hormone secretion in healthy women. Am J Physiol Endocrinol Metab 297: E367-E374, 2009. First published May 26, 2009 doi:10.1152/ajpendo.00230.2009.-Growth hormone (GH) secretion is subject to complex regulation. How pre-and postmenopausal age (PRE, POST), estradiol (E2) availability, and abdominal visceral fat (AVF) jointly affect peptidyl-secretagogue drive of GH secretion is not known. To this end, healthy PRE (n ϭ 20) and POST (n ϭ 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
(77 reference statements)
1
10
1
Order By: Relevance
“…In line with this, impaired GH secretion is reversed following weight loss (Williams et al 1984, Rasmussen et al 1995. Correlative studies assessing the relationship between adiposity and the secretion of GH provide essential information to identify potential factors that suppress GH secretion in obesity (Gill et al 1997, Vahl et al 1997, Veldhuis et al 2009). Recent measures demonstrate that impairments in pulsatile GH secretion in humans precede dietary-induced weight gain (Cornford et al 2011(Cornford et al , 2012 and that the suppression of GH secretion with increased food consumption improves meal tolerance (Cornford et al 2012).…”
Section: Introductionmentioning
confidence: 91%
“…In line with this, impaired GH secretion is reversed following weight loss (Williams et al 1984, Rasmussen et al 1995. Correlative studies assessing the relationship between adiposity and the secretion of GH provide essential information to identify potential factors that suppress GH secretion in obesity (Gill et al 1997, Vahl et al 1997, Veldhuis et al 2009). Recent measures demonstrate that impairments in pulsatile GH secretion in humans precede dietary-induced weight gain (Cornford et al 2011(Cornford et al , 2012 and that the suppression of GH secretion with increased food consumption improves meal tolerance (Cornford et al 2012).…”
Section: Introductionmentioning
confidence: 91%
“…Human studies have shown that growth hormone (GH) levels or secretion are altered in visceral obese individuals with a high cardiometabolic risk (85,239,339,373,375,434,577,589,590,613). Many reports suggested that the association between visceral and/or abdominal obesity is independent of total adiposity (85,339,373,434,613).…”
Section: G Growth Hormonementioning
confidence: 99%
“…al. were analyzing the effects of a 1 year GH-treatment on adult-onset GHD individuals, in tune with the reports of diminishing GH secretion and action with age69, 70. However, the studies on humans completely contradict in vitro studies as well as in vivo observations in GH- transgenic and deficient rodent models which suggest that GH suppresses adiponectin secretion41, 64, 71, 72.…”
Section: Metabolic Effects Of Gh On the Adipose Tissuementioning
confidence: 99%